INTEGRAL EDUCATION IN ANCIENT INDIA FROM VEDAS AND UPANISHADS TO VEDANTA - Ferrer, Albert (International Journal of Research -GRANTHAALAYAH, 2018)
Western scholarship usually ignores the contributions from other civilizations, India for instance. At the same time, contemporary India seems to have forgotten to some extent the deepest achievements of its own tradition. Moreover, modern culture has often produced some kind of despise against ancient traditions as opposed to the freedom and emancipation of the modern world. This paper tries to unveil all the depth and beauty of Indian philosophy of education, especially through major traditions such as Vedas, Upanishads and Vedanta. It also tries to show that the pedagogic message of the sages of modern India revives all the depth of the ancient tradition. This long history of holistic education in India through 35 centuries may enrich the Western insights with figures such as Steiner, Montessori or Dewey, aware that intercultural dialogue will be one of the major challenges of the XXIst century. It becomes crystal clear through this paper that the vision of integral education in Indian culture was inseparable from the spiritual/ mystical dimension, or to put in reverse terms, the spiritual domain constituted the very foundation of the educational process in Indian philosophy of education, a fundamental point that would be again emphasized by Indian modern philosophers such as Vivekananda, Aurobindo and even Krishnamurti.